Duty Cylcing Stratagems for Network Permanency in Wireless Sensor Network - Muhammad Toufique; Hongbo Jiang; Alaa Rahhoom Hadi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Wireless Sensor Networks (WSNs) having Sensor Nodes (SNs) deployed in the field, is penetrating in all fields of life. Commonly used and appreciated by the research community and general user especially. The energy delinquent in WSNs are the main barricades averting whole manipulation expertise. However, their energy embarrassed nature requires the use of energy effective stratagems to maximize network lifetime. Emerging such a Medium Access Control (MAC) code of behavior is burning topic zone in this field. For evade deteriorating imperfect power,   redeemable functions proposed in MAC code of behavior. Features are to save energy and thus extend the lifespan of the network. We exploit especially the duty cycle and present this as an energy minimizing tool in MAC protocols.